Apprenticeships and 'future work': are we ready?. (21st January 2019) - Smith, Erica
Abstract : The paper evaluates the readiness of apprenticeship systems to cope with five major developments affecting the future of work. The institution of apprenticeship has evolved over time in all countries, gradually adapting to changes in industrial processes, the economy, the labour market and education systems. This paper suggests, however, that recent changes in the economy and the labour market, and their concomitant effects on the likely future of work, have the potential to disrupt apprenticeship systems quite radically worldwide, and/or to make them less relevant in the 21st century. The paper draws on data from recent Australian and international research projects undertaken by the author, as well as the author's engagement in Australian government exercises to discuss the future of apprenticeships. The research found that adaptations of systems and processes were being undertaken at company level and by stakeholders such as trade union or employer peak bodies. They were less frequently apparent, however, in government policy. The paper analyses the data to produce a framework of readiness for 'future work', but also queries whether adaptation of apprenticeship systems is necessarily desirable in all instances. Although the presence of multiple stakeholders in the system has previously been viewed as a strength of the system, it can also make even minor changes difficult to implement. This could prove to be a major impediment to apprenticeship's future or could be a means of preserving its essential features.